TPACK’s Understanding Analysis of Physics Teachers in Using Learning Media - Mulhayatiah, Diah; Suhendi, Herni Yuniarti; Windayani, Neneng (Jurnal Pendidikan Progresif, 2020)
Analysis of TPACK’s understanding physics teachers in using learning media. This study aims to determine the use of learning media used by physics teachers in the learning process. This research method is qualitative with research instruments in the form of questionnaires, document analysis and interviews. The study sample consisted of 60 physics teachers in West Java. The results of the study show that the majority of physics teachers still use Power Point media as the main media, then use electronic references, and interactive multimedia. Based on the media compilation process, almost most of them directly use existing media. The main reason is the lack of training gained by teachers in developing learning media. The conclusion of this study is that physics teachers still need technology and pedagogic knowledge in learning. Keywords: content knowledge, ICT, pedagogical knowledge. DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202014